Lateral deformation and buckling analysis of piles including shear effects: Numerical analysis. (15th February 2023) - Fernández-Escobar, Camilo J.; Vega-Posada, Carlos A.; Garcia-Aristizábal, Edwin F.
Abstract: Piles are one-dimensional (1D) beam–column elements used to support tall buildings, onshore and offshore structures, bridges, wind turbines, etc. In practice, piles are commonly designed using the Euler–Bernoulli Theory. However, this theory is only considered appropriate for long, slender piles because it neglects the contribution of the shear deformation on the pile response. The effect of the shear deformation might be of importance in short, rigid and large-diameter piles such as monopiles, and it should be considered in the analysis. In geotechnical engineering, studies addressing this effect and its interaction with the surrounding soil are scarce and very limited. The aim of this work is to conduct a parametric study to investigate the influence of the shear deformation, semi-rigid connections and pile/soil stiffness ratio on the head deflection, head rotation and first-mode of critical load of an embedded pile. For this purpose, the well-known commercial FE software SAP2000 is employed. Four examples are presented to show the effect of the shear deformation on reinforced concrete (RC) and hollow circular piles embedded in either homogeneous or non-homogeneous soil. For lateral deformation analysis, it is found that deflections and rotations at the pile head considerably increase when the shear deformation is taken into account and they are of most significance at low values of pile/soil stiffness ratios. For buckling analysis, Timoshenko's theory shows that the critical load notably increases as the stiffness of the surrounding soil increases and, regardless of the soil/pile stiffness ratio, it rapidly decreases as the shear stiffness of the pile decreases. Highlights: The effects of shear deformation on the lateral response of piles are investigated. The effects of shear deformation on the critical load of piles are examined. The influence of the soil inhomogeneity in conjunction with the effect of shear deformation is examined. Ranges of pile/soil stiffness ratios where shear deformation are of significance are provided. Results from Timoshenko's and Euler–Bernoulli's beam theories are discussed.